Testing of a ground coupled heat pump - Kalogirou, Soteris A.; Florides, Georgios A.; Messaritis, Vassilios (My University, 2010)
A Ground Coupled Heat Pump (GCHP) exploits the ground thermal capacity and the difference in temperature between ambient air and ground with the aid of Ground Heat Exchangers (GHE) for improving its efficiency. The main interest of this study is to determine the efficiency of a ground coupled heat pump used for the acclimatization of a typical office in the Athalassa region, Nicosia, Cyprus and investigate how its efficiency is affected by the operating conditions. The data collection was done in October, 2008 and January, 2009. In summer the results clearly indicate that there is a significant improvement in the sensible capacity over the input power ratio from about 2 to 2.52 when the cooling temperature of the condenser drops from 36.5°C to 22.4°C. In winter, the COP of the pump is 3.6 when the temperature of the evaporator is about 22°C. Significant savings in power can result when GCHPs are used instead of the air-cooled systems.
Keywords: Heat pumps; Energy conversion; Evaporators